The nationalist tendencies in the domestic politics of Mao Zedong (Journal of Oriental Studies, 2016)
This article reveals the essence of internal policy of the Maoists а period of 50-60 years of the 20th century. China’s internal policy of this period was expansionary relative to the small ethnic.
Keywords: China; Maoists; nation-state